Career Trajectories of Municipal Servants: Two Types of Professional Mobility (Case Study in Novgorod Region) - A A Kurakin (RUDN journal of Sociology, 2013)
The case study of a district in the Novgorod region shows some scenarios of recruiting new employees in the district and town municipalities, their work motivation and the most plausible career trajectories. The author argues that on the municipal level (district or its administrative center) there are parallel career ladders for the top-ranked municipal clerks and for the rest of the municipal staff: the career trajectory of the high-ranked clerks can be described as a step-by-step trajectory, while the one of the lower-ranked employees — as a shuttle trajectory. There is an almost insurmountable border line between these two levels of municipal hierarchy, an obstacle for implementing the classical Weberian characteristics of “proper” bureaucracy: meritocratic recruitment and workers’ promotion and predictable long-term career ladders.